Determinan Kejadian Abortus Pada Ibu Hamil Di RSUD dr. Adjidarmo Rangkasbitung - Rita Ariesta (Akademi Kebidanan La Tansa Mashiro, 2021)
The incidence of spontaneous abortion is often stated to be around 10% of all pregnancies. However, this incident is difficult to know with certainty because almost 30% of abortions occur without realizing it. The purpose of this study was to determine the determinants of the incidence of abortion in pregnant women in RSUD Dr Adjidarmo Rangkasbitung in 2017. This type of research method uses case-control with a population of 3483 People. The sample size in this study uses epi info Exe version 7 with Internal Confidence (CI) I 95% so that the Minimum Sample Size (BSM) in this study is 120 cases, 1:1 then the group case 60 people and control group 60 people. The results showed that there was no relationship between the history of abortion, occupation, education and the incidence of abortion, but there was a relationship between maternalage and the incidence of abortion P = 0.00 with OR 4,929, which means that respondents in the age group 20 years/35 years are at almost 5 times greater risk. to experience an abortion when compared with respondents in the age group 20 -35 years. The need for cross-sectoral collaboration by involving various agencies outside of health, including the population and civil registry offices, to prevent pregnancy beyond healthy reproductive age.